2023
DOI: 10.1182/blood.2023019875
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitor inhibits tolerance induction by suppressing terminal exhaustion of donor T cells after allo-HCT

Abstract: Calcineurin inhibitor-based graft-versus-host disease (GVHD) prophylaxis is standard in allogeneic hematopoietic stem cell transplantation (HCT) but fails to induce long-term tolerance without chronic GVHD in a considerable number of patients. In this study, we addressed this long-standing question in mouse models of HCT. After HCT, alloreactive donor T cells rapidly differentiated into PD-1+ TIGIT+ terminally exhausted T cells (terminal-Tex). GVHD prophylaxis with cyclosporine (CSP) suppressed donor T-cell ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Although widespread adoption of prophylaxis with calcineurin inhibitors (CNIs) has improved the rates of acute graft-versus-host-disease (GVHD) following allogeneic hematopoietic stem cell transplantation (allo-HCT), the incidence of chronic GVHD (cGVHD) is rising. 1,2 cGVHD has significant impacts on long-term quality of life and is a primary cause of late morbidity and mortality after allo-HCT. The pathophysiology is complex, involving dysregulation of immune effector populations and disruption of central and peripheral tolerance pathways.…”
Section: Calcineurin Inhibitor Inhibits Tolerance Induction By Suppre...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although widespread adoption of prophylaxis with calcineurin inhibitors (CNIs) has improved the rates of acute graft-versus-host-disease (GVHD) following allogeneic hematopoietic stem cell transplantation (allo-HCT), the incidence of chronic GVHD (cGVHD) is rising. 1,2 cGVHD has significant impacts on long-term quality of life and is a primary cause of late morbidity and mortality after allo-HCT. The pathophysiology is complex, involving dysregulation of immune effector populations and disruption of central and peripheral tolerance pathways.…”
Section: Calcineurin Inhibitor Inhibits Tolerance Induction By Suppre...mentioning
confidence: 99%
“…Senjo et al 1 leverage a mouse model of HCT to explore how CNIs may affect tolerance and development of cGVHD. The authors demonstrated that donor T cells rapidly differentiate into terminally exhausted T cells (Tex) after HCT in the absence of CNI, in part because of upregulation of TOX (thymocyte selection-associated HMG BOX), a master regulator of T-cell exhaustion.…”
Section: Calcineurin Inhibitor Inhibits Tolerance Induction By Suppre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin inhibitors inhibit T-cell exhaustion by inhibiting expression of a master regulator of T cell exhaustion, TOX ( 34 ). In experimental HCT, GVHD prophylaxis with calcineurin inhibitors suppresses differentiation of transitory-Tex to terminal-Tex, resulting in persistent alloreactivity and induction of chronic GVHD ( 35 ). T cell dysfunction of terminal-Tex is irreversible and non-responsive to immune checkpoint inhibitors (ICI), while ICI enhance proliferation and effector functions of Tpex and transitory-Tex ( 36 ).…”
Section: Donor T-cell and Antigen-presenting Cell Interactions Mediat...mentioning
confidence: 99%
“…T cell dysfunction of terminal-Tex is irreversible and non-responsive to immune checkpoint inhibitors (ICI), while ICI enhance proliferation and effector functions of Tpex and transitory-Tex ( 36 ). Therefore, calcineurin-induced transitory-Tex could be a promising therapeutic target to restore GVL effects by ICI but with a risk of GVHD exacerbation ( 35 ).…”
Section: Donor T-cell and Antigen-presenting Cell Interactions Mediat...mentioning
confidence: 99%